Laparoscopic Pyelolithotomy in Children Less Than Two Years Old with Large Renal Stones: Initial Series - Soltani, Mohammad Hossein; Simforoosh, Nasser; Nouralizadeh, Akbar; Sotoudeh, Mehdi; Mollakoochakian, Mohammad Javad; Shemshaki, Hamid Reza (Urology Journal, 2016)
Purpose: Treatment of pediatric urolithiasis is still on debate. This study was designed to evaluate the safety and efficacy of laparoscopic pyelolithotomy in five children less than two years old. Materials and Methods: Five children (less than two years old) with large kidney stones underwent laparoscopic pyelolithotomy. All patients underwent laparoscopic pyelolithotomy via a transperitoneal approach. After medial mobilization of colon and once renal pelvis and ureteropelvic junction were exposed, a longitudinal or circular incision was made on the renal pelvis, depending on the location and shape of the stone. Stones were extracted using an Endobag. Demographic data, size of stones, operation time, duration of hospital stay and stone free rate were assessed. Results: Four boys and a one girl were included in this study. The mean age of patients was 17.6 (range: 13-22) months and the mean duration of operation was 130 (range: 115-145) minutes. The mean size of stone was 24.6 (range: 22-27) mm and the mean duration of hospital stay was 4.4 (range: 4-5) days. Stone free rate was 100%. There was no major complication. Conclusion: Even with a small number of patients, our results seem to show that laparoscopic pyelolithotomy could be a treatment option for selected cases of young pediatric cases with large renal stones. We believe that transperitoneal laparoscopic pyelolithotomy is feasible and it introduces a novel approach for managing kidney stones in pediatric population.